THE IMPACT OF QUANTUM TEACHING LEARNING MODEL WITH PHET MEDIA ON STUDENT LEARNING OUTCOMES FROM DYNAMIC FLUID MATERIALS - Agustini Kholidah Nasution; Lia Afriyanti Nasution; Elia Putri; Rofiqoh Hasan Harahap (Universitas Labuhanbatu, 2023)
This research is motivated by the infrequent use of media and teachers still using the lecture and blackboard method which makes it easy for students to feel bored and bored in the physics learning process at IRA Medan Private High School. The objectives to be achieved are to develop physics learning media with a snake and ladder game using Phet Media Assisted Quantum Teaching on the subject of Dynamic Fluid momentum, to determine the eligibility of validity based on expert assessments, and to know the practicality of media based on student assessments. The stages in development and research include potential and problems, data collection, product design, design validation, and design revision. The product validation stage was validated by 3 validators and students, namely validation by two media experts, one material expert (teacher), and class XI IPA students at SMA IRA Medan. The validation results of the snakes and ladders game using Quantum Teaching Assisted by Media Phet by two validators obtained a score of 4.11 in the appropriate category, and the results of the validation results of the media expert for physics teacher class XI IPA SMA Private IRA Medan obtained a score of 4.23 in the very feasible category, and obtained a score the average of the three experts is 4.15 with a decent category. Based on the responses of the students per aspect, they obtained an average percentage score of 78.67% in the practical category.Keywords: Learning Media, Phet Media Assisted Quantum Teaching, Dynamic FluidsAbstrakPenelitian ini dilatarbelakangi jarangnya penggunaan media dan guru masih menggunakan metode ceramah dan papan tulis membuat siswa mudah merasakan jenuh dan bosan dalam proses pembelajaran fisika di SMA Swsata IRA Medan. Tujuan yang ingin dicapai mengembangkan media pembelajaran fisika dengan permainan ular tangga menggunakan Quantum Teaching Berbantuan Media Phet pada pokok bahasan momentum Fluida Dinamis, mengetahui kelayakan validitas berdasarkan penilaian para ahli, dan mengetahui kepraktisan media berdasarkan penilaian peserta didik.. Tahapan dalam pengembangan dan penelitian meliputi potensi dan masalah, pengumpulan data, desain produk, validasi desain, dan revisi desain. Tahap validasi produk divalidasi oleh 3 validator dan peserta didik yaitu validasi oleh dua ahli media, satu ahli materi (guru), dan peserta didik kelas XI IPA SMA Swsata IRA Medan. Hasil validasi permainan ular tangga menggunakan Quantum Teaching Berbantuan Media Phet oleh dua validator memperoleh skor 4,11 dengan kategori layak, dan hasil validasi ahli media guru fisika kelas XI IPAÂ SMA Swsata IRA Medan memproleh skor 4,23 dengan kategori sangat layak, dan diproleh skor rata-rata ketiga ahli 4,15 dengan kategori layak. Berdasarkan respon peserta didik per aspek memproleh nilai rata-rata persentase sebesar 78,67% dengan kategori praktis.Kata Kunci: Media Pembelajaran, Quantum Teaching Berbantuan Media Phet, Â Fluida Dinamis